Fiscal policy, macroeconomic performance and industry structure in a small open economy - Pål Boug; Thomas Von Brasch; Ådne Cappelen; Roger Hammersland; Håvard Hungnes; Dag Kolsrud; Julia Skretting; Birger Strøm; Trond C. Vigtel (Statistics Norway, Research Department, 2022)
We analyse how fiscal policy affects both the macroeconomy and the industry structure, using a multi-sector macroeconomic model of the Norwegian economy with an inflation targeting monetary policy. Our simulations show that the government spending multiplier in the case of a permanent expansionary fiscal policy coupled with a Taylor-type interest rate rule is around 1 over a ten-year horizon. The corresponding labour tax multiplier is about 0.5. These multipliers are somewhat larger in the case of a transitory fiscal stimulus. The government spending multiplier, in the case of either a permanent or a transitory fiscal stimulus, is considerably larger than 1 when monetary policy is made accommodative by keeping the interest rate fixed. Our simulations also show that the industry structure is substantially affected by an expansionary fiscal policy, as value added in the non-traded goods sector increases at the expense of value added in the traded goods sector. The contraction of activity in the traded goods sector increases when monetary tightening accompanies the fiscal stimulus. Hence, we find that such a policy mix is likely to produce significant de-industrialisation in a small open economy with inflation targeting.
Keywords: E17; E52; E62; 330; Fiscal Policy; Macroeconomy; Industry Structure; Model Simulations